High-strength express bag and preparation method thereof

Through the combination of polylactic acid material and polybutylene succinate material and the use of fiber materials, the problem of low tensile performance of existing express bags is solved, tear resistance and degradation performance are improved, and high-strength express delivery is achieved Bag preparation meets environmental protection and use needs.

CN119119698AInactive Publication Date: 2024-12-13GUANGDONG BAISHENG ENVIRONMENTAL PROTECTION MATERIALS CO LTD

Patent Information

Application Number
CN202411367654.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing biodegradable express bags have low tensile performance and insufficient tear resistance, and cannot effectively carry heavy-duty packages, resulting in inconvenience in use and environmental pollution problems.

Method used

Using a combination of polylactic acid material and polybutylene succinate material, by adjusting its proportion, combining fiber materials and additives, the tensile strength, tear resistance and degradation performance of the express bag are improved, and high-strength express bags are prepared. .

Benefits of technology

It significantly improves the overall carrying capacity of the express bag, prevents breakage and cracking, and achieves an ideal balance of tensile strength, tear resistance and degradation time, meeting environmental protection and use needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119698A_ABST
    Figure CN119119698A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of environment-friendly materials, and mainly relates to a high-strength express bag which comprises a polylactic acid material, a poly (butylene succinate) material, a fiber material and an additive, the mass percent of the polylactic acid material is X, and the unit is%; the mass percentage of the poly (butylene succinate) material is Y, and the unit is%; wherein X + Y = 70; considering that an existing degradable express bag does not have relatively high tensile strength, by adjusting the ratio of the polylactic acid material to the poly (butylene succinate) material, the performance of the express bag in the aspects of tensile strength, tear resistance, thickness, degradation time and the like is optimized, and the optimal effect is achieved; in addition, the precise proportion of natural fibers and specific additives is also fused, so that the comprehensive performance of the express bag is further improved; furthermore, the invention further discloses a preparation method of the high-strength express bag, and the performance of the express bag is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of environmentally friendly materials and mainly relates to a high-strength express bag and a preparation method thereof. Background Art

[0002] As global environmental awareness grows, more and more people are beginning to pay attention to environmental issues. In this context, traditional non-degradable express bags have gradually been strictly restricted by environmental regulations due to their long-term pollution problems. Governments of various countries have introduced relevant policies to reduce the generation of plastic waste and promote the use of green packaging materials. The implementation of these regulations will not only help protect the earth's ecological environment, but also promote the sustainable development of the express delivery industry. Therefore, express delivery companies and related companies have begun to look for and adopt degradable and recyclable environmentally friendly materials to replace traditional plastic express bags to meet the requirements of environmental protection regulations.

[0003] In the current technical field, a variety of preparation methods and products for degradable courier bags have been developed. Many of these products use fiber materials as the main component to enhance the degradability of courier bags. However, these courier bags often have the problem of insufficient tensile strength and are prone to tearing when carrying heavy items, thus affecting the user experience.

[0004] Furthermore, the invention with patent number CN107216537A provides a degradable three-layer plastic courier bag and its preparation method, aiming to further improve the tensile performance through the existing courier bag design. The courier bag includes an outer bag body, a middle bag body and an inner bag body. However, since it only uses a multi-layer courier bag composited with cassava starch and polylactic acid material (lactic acid material), it not only has a significant problem of increased thickness, which makes it inconvenient to use; in addition, although the material is degradable, the tensile strength (30 MPa) and tear resistance (1.2 Newtons per millimeter) of the courier bag are poor, and it cannot withstand the needs of heavy packages.

[0005] Based on this, it is urgent to improve the existing express bag preparation materials and methods to solve the defects of the aforementioned technology. Summary of the invention

[0006] One of the purposes of the present invention is to provide a high-strength express bag to address the deficiencies in the prior art and to solve the technical defect of low tensile performance of degradable express bags in the prior art.

[0007] In order to achieve the above invention objectives, this application adopts the following technical solutions:

[0008] A high-strength express bag, comprising polylactic acid material, polybutylene succinate material, fiber material and additives;

[0009] Specifically, the polylactic acid material is a biodegradable polymer produced by starch fermentation, and its mass percentage is X, in %; the polybutylene succinate material is formed by condensation of butanediol and succinic acid, and its mass percentage is Y, in %;

[0010] Further, wherein X+Y=70.

[0011] The above technical solution has the following technical effects:

[0012] This application takes into account the high tensile strength and rigidity of polylactic acid materials and the excellent flexibility of polybutylene succinate materials, which can provide the material with good ductility and tear resistance. By controlling the proportion of these two materials in the total material preparation, especially the content of polylactic acid materials, the overall carrying capacity of the courier bag can be significantly improved.

[0013] However, polylactic acid material itself has great brittleness, which easily leads to material breakage. To solve this problem, the present application introduces polybutylene succinate material, which is used to supplement the deficiency of polylactic acid material and give the material better flexibility and ductility, thereby effectively preventing the express bag from breaking or cracking during use.

[0014] In addition, the present application also ensures the complementarity and synergistic optimization of material properties by adjusting the ratio between polylactic acid material and polybutylene succinate material, thereby achieving an ideal balance of express bags in terms of tensile strength, tear resistance, thickness and degradation time.

[0015] As a further improvement to the high-strength express bag of the present invention, the mass percentage of the polylactic acid material is 45%-55%; the mass percentage of the polybutylene succinate material is 15%-25%.

[0016] As a further improvement to the high-strength express bag of the present invention, X and Y simultaneously satisfy the following relationship:

[0017] F(X,Y)=0.7(0.8X+0.5Y+40)+0.2(0.1X+0.2Y+1)+0.05(-0.002X-0.003Y+0.35)+0.05(-0.03X-0.04Y+10)

[0018] Among them, the value range of F(X, Y) is 63-67.

[0019] As a further improvement to the high-strength express bag of the present invention, the fiber material is at least one of sisal fiber material, sugarcane fiber material, and bamboo fiber material, and the mass percentage of the fiber material is 10%-20%.

[0020] As a further improvement to the high-strength express bag of the present invention, the mass percentage of sisal fiber material is 5%-10%; the mass percentage of sugarcane fiber material and bamboo fiber material are both 2%-5%.

[0021] As a further improvement to the high-strength express bag of the present invention, the additive is at least one of glycerol monostearate and a coupling agent, and the mass percentage of the additive is 5%-15%.

[0022] As a further improvement to the high-strength express bag of the present invention, the mass percentage of glycerol monostearate is 2%-10%, and the mass percentage of the coupling agent is 2%-5%.

[0023] As a further improvement to the high-strength express bag of the present invention, the preparation material of the high-strength express bag of the present application further includes at least one of cassava starch or corn starch;

[0024] The mass percentages of cassava starch and corn starch are both 2%-5%.

[0025] The second technical purpose of the present application is to design a preparation method that can improve the strength of express bags in order to further solve the defects of existing express bags.

[0026] In order to achieve the above technical objectives, this application adopts the following technical solutions:

[0027] A method for preparing a high-strength courier bag comprising any of the above-mentioned high-strength courier bag preparation materials, the steps of which are as follows:

[0028] S101, drying the polylactic acid material, polybutylene succinate material, fiber material and additives at 80°C-100°C for 2-4 hours to ensure that the raw materials do not contain excessive moisture, wherein the fiber material should be dried to a moisture content of less than 0.5% before adding to the mixture;

[0029] S201, after the polylactic acid material and the polybutylene succinate material are configured to account for 70% of the total material mass percentage, melt-mixing is performed using a twin-screw extruder, wherein the melting temperature is 180° C.-200° C.;

[0030] S301, gradually adding fiber material, additives and other materials to the molten state of the polylactic acid material and the polybutylene succinate material to form a mixture, wherein the mixture is kept uniformly stirred at a temperature of 180° C. for 10-15 minutes;

[0031] S401, extruding the mixture into a film through an extrusion molding machine, the thickness of the film is controlled at 0.2mm-0.3mm, wherein the temperature of the extrusion process is controlled at 180°C-200°C, and the extrusion speed is set to 2-4m / min.

[0032] As a further improvement to the method for preparing the high-strength express bag of the present application, the express bag formed by the film in step S401 is heat-sealed at the bag mouth by an ultrasonic sealing machine, wherein the sealing temperature is 120°C-150°C, and the sealing time is 2s-5s. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0034] Figure 1 The present invention provides a process for preparing a medium- and high-strength express bag. DETAILED DESCRIPTION

[0035] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0036] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0037] Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the claims. Any technical personnel in this field may make several possible changes and modifications without departing from the concept of the present application. Therefore, the scope of protection of the present application shall be based on the scope defined by the claims of the present application.

[0038] The present invention is further described in detail below in conjunction with specific implementation methods, but the embodiments of the present invention are not limited thereto.

[0039] It is known in the prior art that in the field of express packaging, traditional plastic bags have caused serious pollution to the environment due to their non-degradability. With the enhancement of environmental awareness, the development of degradable express bags has become an inevitable trend in the development of the industry. Polylactic acid materials and polybutylene succinate materials are biodegradable materials, and express bags prepared from them can be degraded within an acceptable time after being buried or otherwise treated. However, the present application understands that although polylactic acid materials have good biodegradability, their brittleness limits their application in the field of express bags. In order to overcome this defect, the present application proposes a new type of high-strength express bag, which solves the brittleness problem of polylactic acid materials by introducing polybutylene succinate materials, while maintaining the biodegradability of the materials.

[0040] Specifically, the materials used to prepare the express bag of the present application include polylactic acid materials, polybutylene succinate materials, fiber materials and additives; among them, polylactic acid materials are known for their excellent tensile strength and rigidity, which can give the express bag excellent strength and hardness at a high ratio, significantly enhance its tensile strength, and ensure that the express bag is not easy to tear or break when carrying heavy objects. At the same time, the polybutylene succinate material provides the express bag with good ductility and tear resistance with its excellent flexibility. Especially when the express bag is subjected to external impact or deformation, the addition of polybutylene succinate material effectively reduces the brittleness of the express bag and enhances its resistance to fracture when bent or stretched. Therefore, by mixing these two materials during the preparation process of the express bag, the mechanical properties of the express bag can be significantly improved.

[0041] Furthermore, polylactic acid material is a biodegradable polymer produced by starch fermentation, with a mass percentage of X%, while polybutylene succinate material is formed by the condensation of butanediol and succinic acid, with a mass percentage of Y%. Furthermore, the sum of X and Y is 70%, which ensures that the content of polylactic acid material and polybutylene succinate material in the courier bag is high enough, thus giving the courier bag excellent comprehensive mechanical properties. The high strength and rigidity of polylactic acid material significantly improve the overall bearing capacity of the courier bag, but its greater brittleness is also prone to breakage; the addition of polybutylene succinate material effectively compensates for this defect, providing the necessary flexibility and ductility to prevent the courier bag from breaking or cracking during use. The combination of the two achieves a perfect balance between strength and toughness.

[0042] In the specific implementation process, this application achieves the complementarity of material properties by controlling the total mass percentage of polylactic acid material and polybutylene succinate material to 70%. For example, when the mass percentage of polylactic acid material is 50% and the mass percentage of polybutylene succinate material is 20%, a courier bag with high load-bearing capacity and good impact resistance and toughness can be prepared. At the same time, by optimizing the ratio of polylactic acid material to polybutylene succinate material, the strength and toughness of the courier bag can be improved without increasing the thickness of the material. This shows that under the premise of meeting the same strength requirements, the courier bag can be designed to be thinner, thereby reducing the amount of material used and reducing production costs.

[0043] In addition, the production process of polylactic acid material is based on renewable starch resources, while polybutylene succinate material is produced by polymerizing biodegradable succinic acid and butanediol. The combination of the two enables express bags to degrade quickly after use, effectively reducing environmental pollution.

[0044] Further, the mass percentage of the polylactic acid material is 45%-55%; the mass percentage of the polybutylene succinate material is 15%-25%. In a specific implementation, the mass percentage of the polylactic acid material can be: 45%, 45.5%, 46%, 46.5%, 47%, 47.5%, 48%, 48.5%, 49%, 49.5%, 50%, 50.5%, 51%, 51.5%, 52%, 52.5%, 53%, 53.5%, 54%, 54.5% or 55%. Accordingly, the mass percentage of the polybutylene succinate material can be: 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5%, 20%, 20.5%, 21%, 21.5%, 22%, 22.5%, 23%, 23.5%, 24%, 24.5% or 25%. By adjusting as above, express bags that meet specific performance requirements can be prepared according to different application scenarios and strength requirements.

[0045] Furthermore, the mass percentage parameter of the polylactic acid material satisfies the following relationship with X and Y at the same time:

[0046] F(X,Y)=0.7(0.8X+0.5Y+40)+0.2(0.1X+0.2Y+1)+0.05(-0.002X-0.003Y+0.35)+0.05(-0.03X-0.04Y+10).

[0047] Among them, the F(X,Y) comprehensive performance function is established by optimizing the ratio of polylactic acid material to polybutylene succinate in the present invention. This function aims to balance the tensile strength, tear resistance, thickness and degradation time of the express bag. The weight and formula of each part are formulated based on the experimental data fitting and the actual performance of the material properties. F(X,Y) consists of four parts, and the principles and theoretical basis of each part will be explained in detail below.

[0048] The first part of the F(X, Y) function represents the tensile strength weight (70%), and its formula is 0.8X+0.5Y+40; X in the formula represents the mass percentage of the polylactic acid material, and Y represents the mass percentage of polybutylene succinate. The following is the basis for setting the coefficients in this weight relationship:

[0049] "0.8X" takes into account that the increase of polylactic acid material significantly improves the tensile strength of the courier bag. Because polylactic acid material itself has high strength and rigidity, the contribution coefficient of X to the tensile strength is relatively high (0.8). "0.5Y" takes into account that polybutylene succinate is relatively more flexible. While improving the flexibility of the material, it can also increase the tensile strength to a certain extent. Although the contribution is smaller than that of polylactic acid material, it still has a positive effect. The coefficient of polybutylene succinate is 0.5. "40" This is a constant term fitted by the experiment, which means that even if the ratio of polylactic acid material and polybutylene succinate is not changed, the basic tensile strength of the material under the baseline state.

[0050] The 70% weight is because tensile strength is a key parameter in the performance of express bags, which determines whether the express bags can withstand greater tensile forces or carry heavier items. Therefore, it has a greater weight in the comprehensive performance.

[0051] The second part of the F(X, Y) function represents the tear resistance weight (20%), and its formula is: 0.1X+0.2Y+1.0; the following is the basis for setting each coefficient in this weight relationship:

[0052] "0.1X" takes into account that the increase in polylactic acid material has little effect on improving tear resistance, because polylactic acid material has poor toughness. Although it can improve tensile strength, its effect on tear resistance is limited, so the coefficient of X is low (0.1). "0.2Y" takes into account that the flexibility of polybutylene succinate makes it contribute more to improving tear resistance. The better the toughness of the material, the stronger the tear resistance, so the coefficient of polybutylene succinate is set to 0.2. "1.0" is the basic tear resistance numerical constant, which is based on the data fitted by the actual experiment, indicating the basic tear resistance of the material when the proportion is not adjusted.

[0053] The 20% weight is because tear resistance is another important parameter affecting the durability of courier bags, but its importance is second only to tensile strength, so its weight in the comprehensive performance is relatively low.

[0054] The third part of the F(X, Y) function represents the thickness weight (5%), and its formula is: -0.002X-0.003Y+0.35; the following is the basis for setting the coefficients in this weight relationship:

[0055] Among them, "-0.002X" takes into account that as the proportion of polylactic acid material increases, the thickness of the material increases slightly. Because polylactic acid material is more rigid, more material is required to achieve the same flexibility and processability. Therefore, the coefficient of X is negative (-0.002), indicating that the increase of polylactic acid material will increase the thickness. "-0.003Y" takes into account that the increase in the proportion of polybutylene succinate will further reduce the thickness. The flexibility and ductility of polybutylene succinate make it possible to use less material to achieve the same structural strength and flexibility. Therefore, the coefficient of polybutylene succinate is negative and the absolute value is slightly larger (-0.003). "0.35" is the baseline thickness constant, which indicates the basic thickness of the material when the proportion is not adjusted.

[0056] The 5% weight is because the increase in thickness will affect the performance and material cost of the bag, but the impact on the overall performance is relatively small, so the weight is lower.

[0057] The fourth part of the F(X, Y) function represents the degradation time weight (5%), and its formula is: -0.03X-0.04Y+10; the following is the basis for setting the coefficients in this weight relationship:

[0058] "-0.03X" takes into account that adding polylactic acid material will shorten the degradation time, because polylactic acid material is a material that is easily biodegradable, so X (polylactic acid material ratio) has a significant effect on the degradation time, and the coefficient is negative (-0.03), indicating that as the proportion of polylactic acid material increases, the degradation time shortens. "-0.04Y" takes into account that the degradation of polybutylene succinate is slightly slower than that of polylactic acid material, so its influence coefficient on the degradation time is slightly larger (-0.04), indicating that when the proportion of polybutylene succinate increases, the degradation time of the bag will also be shortened, but the magnitude is slightly greater than that of polylactic acid material. "10" is the basic constant of the degradation time, indicating the basic degradation time of the material when the ratio of polylactic acid material and polybutylene succinate is not adjusted.

[0059] The 5% weight is because although degradation time is very important for environmental protection, in the daily use of express bags, users are more concerned about indicators such as mechanical properties and thickness that directly affect the usage experience, so the weight of degradation time is lower.

[0060] This application optimizes the comprehensive performance of express bags, such as tensile strength, tear resistance, thickness and degradation time, by controlling the ratio of polylactic acid material to polybutylene succinate. By constructing the function F(X,Y), the model calculates the comprehensive performance score based on the ratio of polylactic acid material to polybutylene succinate. The weight setting and formula design of the four parts are based on experimental data fitting and material properties, so that the contribution of each parameter to the performance of the final express bag is clear and controllable.

[0061] Furthermore, the fiber material is at least one of sisal fiber material, sugarcane fiber material, and bamboo fiber material, and the mass percentage of the fiber material is 10%-20%. In the specific implementation process, the mass percentage of the fiber material can be specifically selected as 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5% or 20%. By adjusting the mass percentage of the fiber material, the mechanical properties, thermal stability and durability of the express bag can be optimized.

[0062] Specifically, the mass percentage of the sisal fiber material is 5%-10%, and in the specific implementation process, it can be 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5% or 10%. Among them, when the content of sisal fiber is 10%, the tear resistance of the bag is the best, which can enhance the structural strength of the bag without significantly increasing the thickness of the bag.

[0063] Specifically, the mass percentage of the sugarcane fiber material is 3%-7%. In the specific implementation process, it can be 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5% or 7%. Among these proportions, when the content of sugarcane fiber is 5%, the flexibility of the sugarcane fiber is good, which can significantly improve the flexibility and bending resistance of the bag, and at the same time accelerate the degradation speed of the bag, which meets the environmental protection requirements.

[0064] Specifically, the mass percentage of the bamboo fiber material is 2%-5%, and in the specific implementation process, it can be 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%. Among these proportions, when the content of bamboo fiber is 4%, it can provide additional tensile strength while maintaining the degradation performance of the bag, and will not significantly increase the thickness of the bag or reduce the environmental performance.

[0065] Furthermore, the additive is at least one of glycerol monostearate and a coupling agent, and the mass percentage of the additive is 5%-15%. In the specific implementation process, the mass percentage of the additive can be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or 15%. Among these proportions, when the content of the additive is 10%, it can effectively improve the surface properties of the bag, enhance its moisture resistance and anti-adhesion, and will not have a negative impact on the flexibility and degradation rate of the bag.

[0066] Specifically, glyceryl monostearate is used as a plasticizer to improve the flexibility of the material and reduce the brittleness of the material. The mass percentage of glyceryl monostearate is 2%-10%. In the specific implementation process, it can be 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9% or 10%. Among these proportions, when the content of glyceryl monostearate is 6%, the best surface treatment effect can be achieved, making the bag surface smoother and reducing the friction coefficient.

[0067] Specifically, the coupling agent can improve the compatibility of polylactic acid materials and fiber materials (such as sisal fiber, sugarcane fiber, bamboo fiber), and enhance the overall strength and structural stability of the material. The mass percentage of the coupling agent is 2%-5%. In the specific implementation process, it can be 2%, 2.5%, 3%, 3.5%, 4% or 5%. Among these proportions, when the content of the coupling agent is 3%, the best enhancement effect can be achieved, making the combination between polylactic acid materials and fiber materials closer, improving the tensile strength and tear resistance of the material, and ensuring that the express bag does not delaminate or crack during long-term use.

[0068] Specifically, maleic anhydride grafted polyolefin materials, maleic anhydride grafted polypropylene, silane coupling agents, isocyanate coupling agents, titanate coupling agents, polyolefin elastomers (POE) grafted maleic anhydride, etc. can be selected as coupling agents. In particular, silane coupling agents contain organic groups (such as amino groups, methacryloyloxy groups) and inorganic groups (such as siloxy groups) in their molecules, which enables them to form stable chemical bonds on the surface of the material, thereby effectively combining organic polymers with inorganic materials. Therefore, in actual operation, silane coupling agents, as the preferred material of coupling agents, can significantly enhance the tear resistance and mechanical strength of the material, while reducing the delamination phenomenon. It is worth noting that although this application only uses silane coupling agents as the preferred material of coupling agents, its scope of protection is not limited to silane coupling agents.

[0069] Specifically, in the embodiments of the present application, the silane coupling agent is further preferably 3-glycidyloxypropyltrimethoxysilane (KH-560. As a silane coupling agent, KH-560 has a unique structure that enables it to play a bridging role between the polylactic acid material and the fiber material, thereby improving the comprehensive performance of the composite material. In practical applications, the KH-560 coupling agent is added to the mixed system of the polylactic acid material and the fiber material at a mass percentage of 3%, and after sufficient stirring and mixing, the courier bag is prepared by an extrusion molding process. The experimental results show that the courier bag using the KH-560 coupling agent exhibits excellent performance in terms of tensile strength, tear resistance, durability, etc. In particular, in terms of tensile strength, the value is increased by about 20% compared with the sample without the coupling agent.

[0070] Furthermore, the preparation materials of the express bag of the present application can also be increased with antioxidants. Antioxidants can effectively prevent the material from being degraded due to oxidation during processing and use, and extend the service life of the material. Among them, the mass percentage of the antioxidant is 0.1%-1%. In the specific implementation process, it can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%. In these proportions, when the content of the antioxidant is 0.5%, the best antioxidant effect can be achieved, which effectively inhibits the oxidation reaction of the material in a high temperature and high humidity environment.

[0071] Furthermore, the flame retardant can significantly improve the flame retardant properties of the material and reduce the flammability of the material in a fire. The mass percentage of the flame retardant is 1.5%-3%. In the specific implementation process, it can be 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9% or 3.0%. Among these proportions, when the content of the flame retardant is 1.2%, the best flame retardant effect can be achieved, so that the material has a high self-extinguishing property when encountering a flame, thereby effectively reducing the risk of fire.

[0072] As a further improvement to the high-strength express bag of the present invention, the preparation material of the high-strength express bag of the present application further includes at least one of cassava starch or corn starch;

[0073] The mass percentage of cassava starch and corn starch is 2%-5%. In the specific implementation process, the mass percentage of cassava starch and corn starch is 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%. Among these proportions, when the total content of cassava starch and corn starch is 4%, the best reinforcement effect can be achieved, so that the express bag can maintain good flexibility and degradation speed while improving its tensile strength and impact resistance.

[0074] Furthermore, the preparation materials of the express bag of the present application can also be increased with a light stabilizer. The light stabilizer can effectively prevent the material from undergoing photooxidation when exposed to sunlight for a long time, thereby extending the service life of the material. Among them, the mass percentage of the light stabilizer is 0.1%-1%. In the specific implementation process, it can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%. In these proportions, when the content of the light stabilizer is 0.3%, the best light stabilization effect can be achieved, which effectively inhibits the degradation reaction of the material under ultraviolet irradiation.

[0075] In order to further improve the performance of the express bag of the present application, the present application designs a method for preparing a high-strength express bag according to the above materials and the proportion relationship between the materials, and the steps are as follows:

[0076] S101. Dry the polylactic acid material, polybutylene succinate material, fiber material and additives at 80°C-100°C for 2-4 hours to ensure that the raw materials do not contain excessive moisture. The fiber material should be dried to a moisture content of less than 0.5% before adding to the mixture. The polylactic acid material and polybutylene succinate should be prevented from contacting with moisture in the air before drying to avoid affecting the fluidity of the material after melting.

[0077] Among them, the production should be carried out in a clean and dust-free environment to ensure the purity of the materials and the high quality of the bags. The production workshop should maintain a constant temperature and dryness, and the humidity should be controlled between 50% and 60% to prevent moisture in the air from affecting the processing performance of the materials. In addition, the workshop temperature must be maintained between 20℃ and 25℃ to prevent the operability of material processing from being affected by too high or too low temperature.

[0078] S201, after the polylactic acid material and the polybutylene succinate material are configured to account for 70% of the total material mass percentage, melt-mixing is performed using a twin-screw extruder, wherein the melting temperature is 180° C.-200° C.;

[0079] The melting temperature should be maintained at 180°C-200°C to ensure that the polylactic acid material and polybutylene succinate are fully mixed without material degradation or excessive melting.

[0080] S301, gradually adding fiber material, additives and other materials to the molten state of the polylactic acid material and the polybutylene succinate material to form a mixture, wherein the mixture is kept uniformly stirred at a temperature of 180° C. for 10-15 minutes;

[0081] S401, extruding the mixture into a film through an extrusion molding machine, the thickness of the film is controlled at 0.2mm-0.3mm, wherein the temperature of the extrusion process is controlled at 180°C-200°C, and the extrusion speed is set to 2-4m / min.

[0082] Among them, the extruded film should be quickly cooled to room temperature through a cooling water bath to avoid the material staying at high temperature for too long and ensure the stability of the material.

[0083] In the above preparation process, the preparation device includes a twin-screw extruder, a hot press, and an automatic cutting machine; the twin-screw extruder is mainly used for the melt mixing of polylactic acid materials and polybutylene succinate, requiring uniform mixing effect and sufficient stirring. In addition, the twin-screw extruder can be equipped with a temperature control system, which can accurately control the temperature between 180°C-200°C; the hot press is mainly used for the molding of the film, pressing it into the shape of an express bag, and can control the pressure (5-10 MPa) and temperature (120°C-150°C) to ensure the sealing quality of the bag; the cutting machine is used to cut the film to ensure accurate size and neat cutting.

[0084] Furthermore, the express bag formed in step S401 is heat-sealed at the bag mouth by an ultrasonic sealer, wherein the sealing temperature is 120° C.-150° C. and the sealing time is 2s-5s. The ultrasonic sealer can ensure that the bag mouth does not crack or leak after sealing.

[0085] In order to further highlight the difference between the express bags prepared by the technical solution of the present application and the prior art, the present application adopts different embodiments and comparative examples to test the tensile strength, tear resistance, thickness and degradation time of the express bags prepared by the preparation method of the present application and the existing express bags.

[0086] Among them, the detection method of comparative data is usually tested using internationally and industry-recognized standards and methods. The following are the detection methods and corresponding standards for each indicator:

[0087] Tensile strength refers to the maximum stress that a material can withstand when subjected to a tensile load, measured in megapascals (MPa). For plastics and packaging materials, tensile testing machines are usually used for testing.

[0088] Standard method: According to ISO 527-1:2012 "Determination of tensile properties of plastics" standard.

[0089] Equipment: Tensile testing machine.

[0090] In each embodiment and comparative example of the present application, the steps for testing the tensile strength are as follows:

[0091] S1. Use standard sample shape (such as dumbbell-shaped sample) and specified size (generally 1-3mm thick, 10-20mm wide, and about 100mm long).

[0092] S2. Clamp the sample on a tensile testing machine and stretch it at a specified tensile rate (usually 50 mm / min) until the material breaks, and record the maximum stress value when the material breaks.

[0093] Tear resistance refers to the ability of a material to resist tearing, especially whether the material will break along a certain point when subjected to external force. For film materials, tear tests are often used to determine tear resistance.

[0094] According to ISO 6383-1:1983 "Determination of tear properties of plastic film and sheeting", the trouser tear test method is adopted.

[0095] Equipment: Tear tester or universal material testing machine.

[0096] In each embodiment and comparative example of the present application, the tear resistance testing steps are as follows:

[0097] S1. Prepare standard samples (sample thickness 0.2-1 mm, pre-cut 10 mm before tearing).

[0098] S2. Clamp both ends of the sample in the upper and lower clamps of the tear testing machine.

[0099] S3. Apply tensile force evenly at a specified rate (50 mm / min) until the sample is completely torn.

[0100] S4. Record the average tearing force (in Newtons) required and calculate the tearing force required per millimeter of sample.

[0101] Thickness refers to the thickness value of the material, which is usually measured directly with a thickness gauge. For film materials such as express bags, the uniformity of thickness is closely related to durability.

[0102] Standard method: According to ISO 4593:1993 "Determination of thickness of plastic film and sheet".

[0103] Equipment: Digital thickness gauge or mechanical thickness gauge.

[0104] The steps for detecting thickness in each embodiment and comparative example of the present application are as follows:

[0105] S1. Select a flat, wrinkle-free sample for measurement.

[0106] S2. Place the thickness gauge on the sample, making sure the probe and sample are in steady contact.

[0107] S3. Perform multiple measurements at different locations on the sample and take the average value as the final thickness.

[0108] In addition, for products with high uniformity requirements, measurements must be repeated at multiple locations to ensure the representativeness of the data.

[0109] Degradation time refers to the time required for a material to degrade into carbon dioxide, water and biomass in a natural environment, especially in soil or composting environments, and is usually evaluated using biodegradation tests.

[0110] Standard method: According to ISO 14855-1:2012 "Determination of the ultimate aerobic biodegradation of plastics under controlled composting conditions by measuring the production of carbon dioxide generated" standard.

[0111] Equipment: Biodegradation test chamber or composting test apparatus.

[0112] The steps for detecting the degradation time in each embodiment and comparative example of the present application are as follows:

[0113] S1. The material samples are buried in a biodegradation device that simulates a composting environment. The ambient temperature is maintained at about 58°C and the humidity is controlled at 50%-60%.

[0114] S2. Regularly collect the released carbon dioxide gas and analyze its volume and concentration.

[0115] S3. Calculate the degradation process of the material by analyzing the release rate of carbon dioxide until the material is completely degraded and record the degradation time.

[0116] S4. If simulation tests are conducted in a natural environment, composting or soil burial methods are usually selected to regularly monitor changes in the material's morphology.

[0117] In order to further verify the performance of the materials of this application, this application optimizes and adjusts the mass fraction ratio of polylactic acid material and polybutylene succinate. Based on the adjusted ratio, the corresponding express bags were prepared and tested according to the above preparation method. The test results of Examples 1-5 and Comparative Examples 1-3 are as follows:

[0118] Example 1

[0119] The mass proportions of the components for preparing high-strength express bags are: polylactic acid material: 45%; polybutylene succinate: 25%; sisal fiber: 10%; sugarcane fiber: 5%; bamboo fiber: 5%; glycerol monostearate: 3%; coupling agent (preferably silane coupling: 3-glycidyloxypropyltrimethoxysilane in this embodiment): 3%; cassava starch: 2%; corn starch: 2%.

[0120] Preparation method: Mix according to the above steps S101-S401 to finally obtain a courier bag with balanced performance.

[0121] Example 2

[0122] The mass proportions of the components for preparing high-strength express bags are: polylactic acid material: 50%; polybutylene succinate: 20%; sisal fiber: 10%; sugarcane fiber: 5%; bamboo fiber: 5%; glycerol monostearate: 3%; coupling agent (preferably silane coupling: 3-glycidyloxypropyltrimethoxysilane in this embodiment): 3%; cassava starch: 2%; corn starch: 2%.

[0123] Preparation method: Mix according to the above steps S101-S401 to finally obtain a courier bag with balanced performance.

[0124] Example 3

[0125] The mass proportions of the components for preparing high-strength express bags are: polylactic acid material: 55%; polybutylene succinate: 15%; sisal fiber: 10%; sugarcane fiber: 5%; bamboo fiber: 5%; glycerol monostearate: 3%; coupling agent (preferably silane coupling: 3-glycidyloxypropyltrimethoxysilane in this embodiment): 3%; cassava starch: 2%; corn starch: 2%.

[0126] Preparation method: Mix according to the above steps S101-S401 to finally obtain a courier bag with balanced performance.

[0127] Example 4

[0128] The mass proportions of the components for preparing high-strength express bags are as follows: polylactic acid material: 50%; polybutylene succinate: 25%; sisal fiber: 10%; sugarcane fiber: 5%; bamboo fiber: 5%; glycerol monostearate: 3%; coupling agent (preferably silane coupling in this embodiment: 3-glycidyloxypropyltrimethoxysilane): 2%;

[0129] Preparation method: Mix according to the above steps S101-S401 to finally obtain a courier bag with balanced performance.

[0130] Example 5

[0131] The mass proportions of the components for preparing high-strength express bags are as follows: polylactic acid material: 45%; polybutylene succinate: 20%; sisal fiber: 10%; sugarcane fiber: 5%; bamboo fiber: 5%; glycerol monostearate: 3%; coupling agent (preferably silane coupling: 3-glycidyloxypropyltrimethoxysilane in this embodiment): 3%; cassava starch: 2%; corn starch: 2%; flame retardant: 2%; light stabilizer: 1%; antioxidant: 1%.

[0132] Preparation method: Mix according to the above steps S101-S401 to finally obtain a courier bag with balanced performance.

[0133] Comparative Example 1

[0134] The mass proportions of the components for preparing high-strength express bags are as follows: polylactic acid material: 30%; polybutylene succinate: 15%; sisal fiber: 15%; sugarcane fiber: 7%; bamboo fiber: 7%; glycerol monostearate: 3%; coupling agent (preferably silane coupling: 3-glycidyloxypropyltrimethoxysilane in this embodiment): 3%; cassava starch: 4%; corn starch: 4%; flame retardant: 2%; light stabilizer: 5%; antioxidant: 5%.

[0135] Preparation method: Mix according to the above steps S101-S401 to finally obtain a courier bag with balanced performance.

[0136] Comparative Example 2

[0137] The mass proportions of the components for preparing high-strength express bags are as follows: polylactic acid material: 30%; polybutylene succinate: 25%; sisal fiber: 5%; sugarcane fiber: 7%; bamboo fiber: 7%; glycerol monostearate: 3%; coupling agent (preferably silane coupling: 3-glycidyloxypropyltrimethoxysilane in this embodiment): 3%; cassava starch: 4%; corn starch: 4%; flame retardant: 2%; light stabilizer: 5%; antioxidant: 5%.

[0138] Preparation method: Mix according to the above steps S101-S401 to finally obtain a courier bag with balanced performance.

[0139] Comparative Example 3

[0140] The weight proportions of the components used to prepare the high-strength express bag are as follows: polylactic acid material: 45%; polybutylene succinate: 30%; sisal fiber: 5%; sugarcane fiber: 3%; bamboo fiber: 7%; glycerol monostearate: 3%; coupling agent (preferably silane coupling: 3-glycidyloxypropyltrimethoxysilane in this embodiment): 3%; cassava starch: 4%;

[0141] Preparation method: Mix according to the above steps S101-S401 to finally obtain a courier bag with balanced performance.

[0142] In order to verify the use effect of the high-strength express bag made of the biodegradable material of the present invention, the tensile strength, tear resistance, thickness and degradation time of each embodiment and comparative example product were tested; the testing methods are as follows: (1) Tensile strength test: according to ISO 527-1:2012 "Determination of tensile properties of plastics" standard; (2) Tear resistance test: according to ISO 6383-1:1983 "Determination of tear properties of plastic films and sheets" standard; (3) Thickness test: according to ISO 4593:1993 "Determination of thickness of plastic films and sheets" standard; (4) Degradation time test: according to ISO 14855-1:2012 "Determination of final aerobic biodegradation of plastics by measuring the production of carbon dioxide generated under controlled composting conditions" standard.

[0143] The test results of the express bags in Examples 1-5 and Comparative Examples 1-3 are shown in Table 1 below:

[0144]

[0145] Table 1

[0146] According to the contents of Table 1, when the sum of X and Y satisfies 70 and meets the adjustment range of F(X, Y), the comprehensive performance of the courier bag is the best. Specifically, it can be seen from Table 1 that the courier bags of Examples 1 to 5 are superior to Comparative Examples 1-3 in terms of tensile strength and tear resistance. This shows that by optimizing the mass fraction ratio of polylactic acid material and polybutylene succinate, the mechanical properties of the courier bag can be significantly improved. Among them, Example 3 has the highest tensile strength, reaching 62 MPa, and the tear resistance also reaches 2.8 Newtons / mm, showing excellent mechanical properties.

[0147] In terms of thickness, the thickness of the courier bags from Example 1 to Example 5 is between 0.24 mm and 0.28 mm, which is significantly lower than 1.5 mm of Comparative Example 1 and 1.2 mm of Comparative Example 2. In addition, the test data of Comparative Example 3 shows that since the sum of X and Y is not controlled at 70, it actually exceeds this value, resulting in its thickness far exceeding that of Examples 1-5 and Comparative Example 1-2, which in turn affects the degradation time of the courier bags. Therefore, the above experimental data reveals that by optimizing the formula, we can achieve the thinness of courier bags while ensuring mechanical properties, thereby reducing material consumption and transportation costs.

[0148] In terms of degradation time, the degradation time of the courier bags of Examples 1 to 5 is between 6 and 9 months, which meets the environmental protection requirements of biodegradable materials. The degradation time of Comparative Example 3 is as long as 9 to 11 months, which shows that by adjusting the mass fraction ratio of polylactic acid material and polybutylene succinate, the mechanical properties and thickness of the courier bag can be optimized without affecting the degradation performance.

[0149] In summary, by adjusting the mass fraction ratio of polylactic acid material and polybutylene succinate, the comprehensive performance of the courier bag, including mechanical properties, thickness and degradation time, can be effectively improved. The formula of Example 3 (which satisfies the condition of X+Y=70 and the adjustment range of F(X, Y)) performs best in terms of comprehensive performance, has high tensile strength and tear resistance, and maintains a short degradation time, which is a more ideal courier bag material formula.

[0150] The above are only preferred embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A high-strength express bag, characterized in that: Including polylactic acid materials, polybutylene succinate materials, fiber materials and additives; The polylactic acid material is a biodegradable polymer produced by starch fermentation, and its mass percentage is X, in %; The polybutylene succinate material is formed by polycondensation of butanediol and succinic acid, and its mass percentage is Y, in %; Among them, X+Y=70.

2. The high-strength express bag according to claim 1, characterized in that: The mass percentage of the polylactic acid material is 45%-55%; the mass percentage of the polybutylene succinate material is 15%-25%.

3. The high-strength express bag according to claim 1, characterized in that: X and Y satisfy the following relationship at the same time: F(X,Y)=0.7(0.8X+0.5Y+40)+0.2(0.1X+0.2Y+1)+0.05(-0.002X-0.003Y+0.35)+0.05(-0.03X-0.04Y+10) Among them, the value range of F(X, Y) is 63-67.

4. The high-strength express bag according to claim 1, characterized in that: The fiber material is at least one of sisal fiber material, sugarcane fiber material and bamboo fiber material, and the mass percentage of the fiber material is 10%-20%.

5. The high-strength express bag according to claim 4, characterized in that: The mass percentage of the sisal fiber material is 5%-10%; the mass percentage of the sugarcane fiber material and the bamboo fiber material are both 2%-5%.

6. The high-strength express bag according to claim 1, characterized in that: The additive is at least one of glycerol monostearate and a coupling agent, and the mass percentage of the additive is 5%-15%.

7. The high-strength express bag according to claim 6, characterized in that: The mass percentage of glycerol monostearate is 2%-10%, and the mass percentage of the coupling agent is 2%-5%.

8. The high-strength express bag according to any one of claims 1 to 7, characterized in that: Also including at least one of tapioca starch or corn starch; The mass percentages of the cassava starch and the corn starch are both 2%-5%.

9. A method for preparing a high-strength express bag, characterized in that: The high-strength express bag preparation material comprising any of claims 1 to 8 comprises the following steps: S101, drying the polylactic acid material, polybutylene succinate material, fiber material and additives at 80°C-100°C for 2-4 hours to ensure that the raw materials do not contain excessive moisture, wherein the fiber material should be dried to a moisture content of less than 0.5% before adding to the mixture; S201, after the polylactic acid material and the polybutylene succinate material are configured to account for 70% of the total material mass percentage, melt-mixing them using a twin-screw extruder, wherein the melting temperature is 180° C.-200° C.; S301, gradually adding fiber material, additives and other materials to the molten state of the polylactic acid material and the polybutylene succinate material to form a mixture, wherein the mixture is uniformly stirred at a temperature of 180° C. for 10-15 minutes; S401, extruding the mixture into a film through an extrusion molding machine, wherein the thickness of the film is controlled at 0.2 mm-0.3 mm, wherein the temperature of the extrusion process is controlled at 180° C.-200° C., and the extrusion speed is set to 2-4 m / min.

10. The method for preparing a high-strength express bag according to claim 9, characterized in that: The express bag formed in step S401 is heat-sealed at its mouth by an ultrasonic sealing machine, wherein the sealing temperature is 120° C.-150° C. and the sealing time is 2s-5s.

Citation Information

Patent Citations

  • Polylactic acid / fatty dibasic acid and diol polyester composite

    CN102108194A

  • Degradable express bag material

    CN107955251A

  • Naturally-degradable plastic bag and production process thereof

    CN113789038A

  • Bamboo fiber-based degradable environment-friendly material and preparation method thereof

    CN115785634A

  • Biodegradable nano composite material as well as preparation method and application thereof

    CN117986825A

Cited By

  • Degradable and recyclable express bag and preparation method thereof

    CN120024096A

  • Degradable and recyclable express bag and preparation method thereof

    CN120024096B

  • Degradable bamboo fiber express packaging bag and preparation method thereof

    CN120904538A